Data Flood Helping the Navy Address the Rising Tide of Sensor Information - Porche, Isaac R. III (RAND Corporation, 2014)
Navy analysts are struggling to keep pace with the growing flood of data collected by intelligence, surveillance, and reconnaissance sensors. This challenge is sure to intensify as the Navy continues to field new and additional sensors. The authors explore options for solving the Navy's "big data" challenge, considering changes across four dimensions: people, tools and technology, data and data architectures, and demand and demand management.